Ensuring Justice for People With Intellectual Disabilities in Criminal Procedure - Vu, Cong Giao (H. : ĐHQGHN, 2019)
The paper analyses the conditions for guaranteeing justice for people with intellectual disabilities. As argued by the authors, justice is a highly generalized category, reflecting the combined value system, relating to social morality, politics, law and the operation of the state apparatus. A person who wants access to justice must understand and apply the whole of factors such as the legal system and law enforcement institutions. Meanwhile, people with intellectual disabilities are those with special cognitive disabilities, making it difficult for them to understand and apply the stated factors. This requires that in addition to their own efforts, they need to have the support of the state, society and family to ensure access to justice. Access justice is a very important right of people with disabilities. Ensuring access to justice in criminal proceedings is to ensure their rights, benefits, and dignity as a vulnerable group of people in society.